2016
DOI: 10.1080/21645515.2016.1244592
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-specific IgG as a mediator of allergy inhibition: Lessons from mother to child

Abstract: Allergen-specific IgG produced by immune mothers is associated with less predisposition to allergy development in their children. This finding has been described by several groups over the last few decades, but the mechanisms by which maternal IgG can inhibit allergy development are still not fully understood. With the purpose of summarizing past investigations, we review the literature on murine models of maternal immunization with allergens and on immune regulation in humans after passive therapy with purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…The investigation of IgG from patients with AD as the mediator of an inflammatory profile of iNKT cells during its maturation is based on the hypothesis which proposes that IgG antibodies can interact with receptors expressed by immature cells resulting in functional modulation . In our study, IgG was purified from patients with moderate or severe AD due to the observation that these patients have a higher frequency of peripheral iNKT cells compared to patients with mild grade …”
Section: Discussionmentioning
confidence: 99%
“…The investigation of IgG from patients with AD as the mediator of an inflammatory profile of iNKT cells during its maturation is based on the hypothesis which proposes that IgG antibodies can interact with receptors expressed by immature cells resulting in functional modulation . In our study, IgG was purified from patients with moderate or severe AD due to the observation that these patients have a higher frequency of peripheral iNKT cells compared to patients with mild grade …”
Section: Discussionmentioning
confidence: 99%
“…Regulation of allergy development in murine offspring mediated by maternal and neonatal immune status has been discussed by our group . Recent observations have highlighted the concept of the neonatal window of opportunity and the critical role of early priming for lifelong host‐microbiota and immune homoeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of allergy development in murine offspring mediated by maternal and neonatal immune status has been discussed by our group. [1][2][3][4][5] Recent observations have highlighted the concept of the neonatal window of opportunity and the critical role of early priming for lifelong host-microbiota and immune homoeostasis. 6 Microbial factors have a strong impact on the development of immune cells, including CD8 + T cells, B cells, invariant natural killer T (iNKT) cells and γδ T cells.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the authors suggested that maternal immunization could influence intrathymic maturation of lymphocytes on offspring . Two years later, we proposed a hypothesis named “MatIgG primary modulation theory” that questioned whether IgG could directly influence the maturation of lymphocytes on primary organs such as thymus and bone marrow …”
Section: Introductionmentioning
confidence: 99%